Deletion Involving the 7q31-32 Band at the CADPS2 Gene Locus in a Patient with Autism Spectrum Disorder and Recurrent Psychotic Syndrome Triggered by Stress - Grabowski, Paulo André Pera; Bello, Alexandre Ferreira; Rodrigues, Diogo Lima; Forbeci, Murilo José; Motter, Vinicius; Raskin, Salmo (Case Reports in Psychiatry, 2017)
Autism spectrum disorder (ASD) is a neurodevelopmental disorder marked by impairments in social functioning, language, communication, and behavior. Recent genome-wide association studies show some microdeletions on the 7q31-32 region, including the CADPS2 locus in autistic patients. This paper reports the case of a patient with ASD and recurrent psychotic syndrome, in which a deletion on the 7q31-32 band at the CADPS2 gene locus was evidenced, as well as a brief review of the literature on the CADPS2 gene and its association with ASD.